A B-ARR-mediated cytokinin transcriptional network directs hormone cross-regulation and shoot development - Mingtang Xie (Nature Portfolio, 2018)
Cytokinin regulates gene expression by activation of ARR transcription factors. Here, the authors use ChIP-seq to show how three type B-ARRs mediate cytokinin response in Arabidopsis and provide evidence that cytokinin regulates meristem development by promoting B-ARR binding to WUSCHEL.